Donor‐derived Kaposi's sarcoma in a liver–kidney transplant recipient. Issue 2 (25th October 2017) - Dollard, S. C.; Douglas, D.; Basavaraju, S. V.; Schmid, D. S.; Kuehnert, M.; Aqel, B.
Abstract : Human herpes virus 8 (HHV‐8), also known as Kaposi's sarcoma associated herpesvirus (KSHV), is an oncogenic virus that can cause Kaposi's sarcoma (KS). KS can develop following organ transplantation through reactivation of the recipient's latent HHV‐8 infection, or less commonly through donor‐derived infection which has higher risk for severe illness and mortality. We describe a case of probable donor‐derived KS in the recipient of a liver–kidney transplant. The donor had multiple risk factors for HHV‐8 infection. The KS was successfully treated by switching immunosuppression from tacrolimus to sirolimus. With an increasing number of human immunodeficiency virus (HIV)‐positive persons seeking organ transplantation and serving as organ donors for HIV‐positive recipients, HHV‐8 prevalence among donors and recipients will likely increase and with that the risk for post‐transplant KS. Predetermination of HHV‐8 status can be useful when considering organ donors and recipients with risk factors, although there are currently no validated commercial tests for HHV‐8 antibody screening. Abstract : With increasing numbers of human immunodeficiency virus–positive individuals receiving organ transplants, and in some cases serving as organ donors, greater awareness of the risk factors for posttransplant Kaposi's sarcoma and measures to reduce its occurrence may be warranted.